Detection of vowel transition regions from Hindi language. (November 2021) - Yadav, Jainath
Highlights: The vowel transition regions lie in the junction between a consonant and vowel (CV) regions and between a vowel and a consonant (VC) regions. We have proposed a method for determining the vowel transition regions based on the rate of change of formant frequencies using zero-time windowing and numerator of group-delay function. Zero-time windowing derives the instantaneous formant frequencies accurately at every sample location due to contribution of that sample itself. The numerator of group-delay function enhances the formant frequencies. The proposed transition region detection method is evaluated on CV, CVC and TIMIT databases and it has shown significant improvement in the performance compared to the existing method. Abstract: The vowel transition regions are the crucial landmarks in the speech signal. These vital regions are present at both ends of the vowel. They lie in the junction between a consonant and a vowel (CV) regions. This region plays an important role in numerous speech applications like speaker recognition, emotion conversion, speech rate modification, and CV unit recognition. The performance of these applications crucially depends on the accuracy of the estimation of vowel transition regions. In this paper, we have proposed a method for determining the transition regions based on the rate of change of formant frequencies using zero-time windowing and numerator of the group-delay function. Zero-time windowing derives the instantaneous formant frequencies accurately at every sample location due to the contribution of that sample itself. The numerator of the group-delay function enhances the formant frequencies. The proposed transition region detection method is evaluated on CV, and continuous speech databases recorded in the Hindi language. The proposed method has shown around 12% improvement in accuracy compared to the existing method.